Relationship Between Knowledge Level and Compliance Towards the Importance of Sunscreen use in Pharmacy Students of University of Muhammadiyah Kuningan - Hanifah, Rakhmawati; Vera Mulyawantie; Suci Purwaningsih (Frontiers in Sustainable Science and Technology, 2025)
Excessive exposure to UV rays from the sun on the skin can cause problems such as premature aging, sunburn, and even skin cancer. Sunscreen is a cosmetic used as a way to protect the skin from sun exposure. This study aims to determine the relationship between the level of knowledge and compliance with the importance of using sunscreen in Pharmacy Students at the Muhammadiyah University of Kuningan. The type of research used in this study is observational analytic using a cross-sectional design. This study uses a purposive sampling technique for sample selection. The population in this study was 184 people with a sample size of 65 people. Data analysis used was univariate and bivariate analysis. The results of the study on the level of knowledge and compliance with the use of sunscreen in Pharmacy Students at the Muhammadiyah University of Kuningan, have a level of knowledge of 57% in the fairly good category, and compliance with the use of sunscreen of 57% in the compliant category. The results of the Spearman rank test on the data on the relationship between the level of knowledge and compliance obtained a significance value of 0.158, meaning that there is no relationship between the level of knowledge and compliance with the use of sunscreen in Pharmacy Students at the Muhammadiyah University of Kuningan.